Nurse Job Satisfaction: Perspectives from Salary, Mentorship to Career Development - Yuyun Tafwidhah; Muhammad Ali Maulana; I Made Moh. Yanuar Saifudin (Indonesian Journal of Global Health Research, 2026)
Nurse job satisfaction is an important determinant of workforce stability, quality of care, and organizational performance. Teaching hospitals present a distinctive work environment due to their dual role in the delivery of healthcare services and clinical education, which may influence nurses perceptions of satisfaction differntly. This study aimed to explore nurses job satisfaction in a teaching hospital and to examine motivational and hygiene related factors associated with job satisfaction based on Herzberg’s two factor theory. A quantitaive descriptive study was conducted among 69 nurses at a teaching hospital in Pontianak City, Indonesia. Participants were recruited using concecutive sampling. Data were collecting using an online questionnair based on Herzberg’s motivation hygiene framework. Descriptive statistik and Spearman correlation anayses were performed. Most nurses reported being satisfied with their job. Hygiene-related factors, particularly the alignment of pay and incentives with workload and the timeliness of payment, showed the strongest relationship with job satisfaction. Motivational factors, including career development and supervisor evaluation showed a moderate relationship. Nurses’ job satisfaction in the teaching hospital setting is primarily associated with compensation-related factors, followed by career development and supervisory support. This study contributes empirical evidence on the relevance of Herzberg’s two-factor theory in understanding nurse job satisfaction within the teaching hospital context.